Non-invasive intradialytic percutaneous perfusion monitoring: a view to the heart through the skin - Penny, Jarrin D.; Hur, Lisa; Salerno, Fabio R.; Wong, Dickson; Jan, M. Hussain; McIntyre, Christopher W. (Frontiers in Nephrology, 2023)
Introduction: The life sustaining treatment of hemodialysis (HD) induces recurrent and cumulative systemic circulatory stress resulting in cardiovascular injury. These recurrent insults compound preexisting cardiovascular sequalae leading to the development of myocardial injury and resulting in extremely high morbidity/mortality. This is largely a consequence of challenged microcirculatory flow within the myocardium (evidenced by detailed imaging-based studies). Currently monitoring during HD is performed at the macrovascular level. Non-invasive monitoring of organ perfusion would allow detection and therapeutic amelioration of this pathophysiological response to HD. Non-invasive percutaneous perfusion monitoring of the skin (using photoplethysmography - PPG) has been shown to be predictive of HD-induced myocardial stunning (consequence of segmental ischemia). In this study we extended these observations to include a dynamic assessment of skin perfusion during HD compared to directly measured myocardial perfusion during dialysis and cardiac contractile function. Methods: We evaluated the intradialytic microcirculatory response in 12 patients, receiving conventional HD treatments, using continuous percutaneous perfusion monitoring throughout HD. Cardiac echocardiography was performed prior to the initiation of HD and again at peak HD-stress to assess the development of regional wall motion abnormalities (RWMA). Myocardial perfusion imaging was obtained at the same timepoints (pre-HD & peak-HD stress), utilizing intravenous administered contrast and a computerized tomography (CT) based method. Intradialytic changes in pulse strength (derived from PPG) were compared to the development of HD-induced RWMAs (indicative of myocardial stunning) and changes in myocardial perfusion. Results: We found an association between the lowest pulse strength reduction (PPG) and the development of RWMAS (p=0.03) as well as with changes in global myocardial perfusion (CT) (p=0.05). Ultrafiltration rate (ml/kg/hr) was a significant driver of HD-induced circulatory stress [(associated with greatest pulse strength reduction (p=0.01), reduction in global myocardial perfusion (p=0.001), and the development of RWMAs (p=0.03)]. Discussion: Percutaneous perfusion monitoring using PPG is a useful method of assessing intradialytic hemodynamic stability and HD-induced circulatory stress. The information generated at the microcirculatory level of the skin is reflective of direct measures of myocardial perfusion and the development of HD-induced myocardial stunning. This approach warrants additional evaluation for the detection and management of HD-induced cardiac injury.